Hybrids of arenobufagin and benzoisoselenazol reducing the cardiotoxicity of arenobufagin. Issue 20 (1st November 2018) - Hou, Wen; Huang, Zhi-Xing; Xu, Hong-Gui; Lin, Jing; Zhang, Dong-Mei; Peng, Qun-Long; Lin, Hui; Chang, Yi-Qun; Wang, Long-Hai; Yao, Zhe; Sun, Ping-Hua; Chen, Wei-Min
Graphical abstract: A series of novel benzoisoselenazol-containing arenobufagin hybrids were designed, synthesized and their in vitro cytotoxicity for cancer cell lines and AC16 cell line, as well as their ROS scavenge activities were evaluated. Among them, 6d and6f exhibited ROS scavenge activities and less cardiotoxcity. Highlights: A series of novel benzoisoselenazol-containing arenobufagin hybrids (6a –6f ) were synthesized by employing a linker of natural amino acid. The in vitro cytotoxicity against three human cell lines and ROS scavenge activities were tested. Two hybrids (6d and6f ) with well ROS scavenge activities and less cardiotoxicity were identified. Abstract: Arenobufagin is a naturally occurring bufadienolide showing promising antitumor activity accompanied however with apparent cardiac toxicity. Following the recent discovery that oxidative damage possibly be an important cause of the cardiac toxicity of cardenolides, a strategy fusing the antitumor agent arenobufagin with a benzoisoselenazol fragment, a reactive oxygen species (ROS) scavenger, has been developed. Six novel hybrids were synthesized and their ROS scavenging activities as well as their in vitro cytotoxicity against the human hepatocellular carcinoma cell line HepG2, an adriamycin-resistant subline HepG2/ADM, and the human myocardial cell line AC16 were evaluated. The results indicate that the hybrids exhibit various degrees of in vitro ROS scavenging activities, and weaker cytotoxicity than that of arenobufagin against the myocardial cell line AC16. These findings suggest the feasibility of a strategy in which the cardiotoxicity of the potential antitumor agent arenobufagin is reduced.